Light and electron microscopic study of Indian pashmina (cashmere) fibre - SOMVANSHI, R; KOUL, G L; BISWAS, J C (The Indian Journal of Animal Sciences, 2013)
Light and electron microscopy of Indian pashmina fibre (cashmere) was studied. Depth of hair follicles (primaries) was more than double to that of pashmina fibres (secondaries). Horizontal sections of skin showed trio of primaries, secondaries, sweat and sehaceous glands and erector muscle. The central primary follicle was generally larger than the lateral primaries. The scanning electron microscopy (SEM) of fibres had pointed tip, shaft and root papilla. The root papillae varied from kidney to wedge shape. Fibre shafts were 9 to 10mu m thick, but most of the fibres were 12 to 16 pm thick. The shaft was distinct, smooth, encircled by scales, rolled impressions of it revealing the form of waved mosaic pattern. Tip of fibre showed a taperingend with its surface uneven and rough. Wax-like amorphous secretory product was observed on root papillae, shaft and tip. Transmission Electron Microsopy (TEM) showed that pashmina fibres were almost circular in cross-section, and comprised cuticle and cortex. The cuticle and cortex were clearly demarcated by a thin electron dense zone. Cortex contained cords of epidermal cells without marked nuclei. The onhoand para-cortical zones could not be differentiated.